The Effectiveness of Cooperative Learning Model Assisted by Learning Management System in Improving Learning Outcomes - Novitasari, Dewiana; Samsudin; Lumbantoruan, Jitu Halomoan; Simorangkir, Yosua Novembrianto; Pramono, Tias (Jurnal Pedagogi dan Pembelajaran, 2024)
The decline in student understanding and learning outcomes in courses is caused by the learning model and media as tools used in delivering the material are less than optimal. The gap between theory, expectations, and reality in the field makes this research urgent to be researched to improve student understanding and learning outcomes in courses using cooperative learning models with the help of a Learning Management System (LMS). The research method used is Research and development (R&D) with the ADDIE method. The research subjects were 40 students. The product developed is a cooperative learning model. Data collection techniques using product validation, instruments, pre-test, and post-test. Data analysis techniques start from needs analysis, design, development, testing, and evaluation. The results of data validation, tests, and assessment instruments are analyzed in stages until the product is declared valid, practical, and effective. As a result, the technology expert's score was 92.13, the learning model expert's score was 91.43, the peer assessment was 94.02, and all the assessments given were interpreted very well. In small trials, the average post-test result was 88.40. The average score for the large-group trial was 90.83. The difference in scores between students who used the model and those who did not use the model was 18.63. In conclusion, the product developed can increase understanding and student learning outcomes increase significantly in courses.